Exploring the connections between students' motivation, self efficacy, personality, and academic achievement through ordinary least squares estimation / Mohd Azry Abdul Malik ... [et al.] - Abdul Malik, Mohd Azry; Ghazali, Jasrul Nizam; Rusli, Alya’ Nabihah; Sabaruddin, Nur Syahirah Alya; Ahmad Huzami, Nurin Adriana; Ismail, Nurul Syahira; Zakaria, Surhana Amani; Suhaimin, Mohd Faiez; Sahroni, Mohamad Norzamani (Unit Penerbitan UiTM Kelantan, 2024)
The inability to anticipate students’ academic performance may lead to insufficient preparation upon facing upcoming global challenges. This study aims to measure the relationship between students’ motivation, self-efficacy, and personality on academic achievement. Additionally, the study aims to compare students’ academic achievement levels between different genders. Employing simple random sampling with a 95% confidence level and a 10% margin of error, the study involved 78 participants from the Diploma in Mathematical Science program at a prominent higher education campus in Kelantan, Malaysia. Data collection was done through self-administered questionnaires, and data analysis employed ordinary least squares estimation and an independent t-test. The findings reveal only Motivation (p-value = 0.041) has significant relationships with students’ academic achievement. Notably, no discernible differences in academic achievement were observed between genders (p-value = 0.913). The study offers valuable insights for higher education administrators and policymakers seeking to enhance students’ academic achievement.